Real-world eligibility for platinum doublet plus immune checkpoint inhibitors in extensive-stage small-cell lung cancer - Rittberg, Rebekah; Leung, Bonnie; Al-Hashami, Zamzam; Ho, Cheryl (Frontiers in Oncology, 2022)
Introduction: Small cell lung cancer (SCLC) is a rapidly progressing aggressive malignancy. Durvalumab in CASPIAN and atezolizumab in IMPower133 were found to improve overall survival (OS) for extensive stage SCLC. Here we evaluate the proportion of real-world ES SCLC patients who may be eligible for first line immune checkpoint inhibitor (ICI) with platinum-doublet. Methods: A retrospective cohort analysis was conducted of referred ES SCLC between 2015-2017 in British Columbia, Canada. Patient demographics, staging, treatment, and survival data were collected through the Cancer Registry. Retrospective chart review was completed to extract past medical history and missing variables. CASPIAN/IMPower133 excluded patients with autoimmune diseases, active infection, and performance status (PS) ≥2. Results: Between 2015-2017, 349 patients were diagnosed with ES SCLC. In patients who received platinum doublet chemotherapy (n=227) 15 had medical contraindication to ICI: inflammatory bowel disease (n=4), rheumatoid arthritis (n=4), idiopathic pulmonary fibrosis (n=3), lupus (n=1), Sjogren’s (n=1), Takayasu arteritis (n=1), active tuberculosis (n=1). ECOG PS was 0-1 in 96 (45%), PS was 2 in 61 (29%) and ≥3 in 51 (10%). Prior to cycle 1, 82 (36%) patients were eligible for ICI in addition to platinum doublet, 23% of the entire ES population. After cycle 1 and 2, and additional 15 (7%) and 8 (4%) patients became PS 0-1 respectively. mOS for ES SCLC who received first line platinum doublet, non-platinum chemotherapy and best supportive care was 8.4 1.9 and 1.5 months, (p<0.001). Discussion: By CASPIAN/IMpower133 trial eligibility, only 36% of our real-world platinum treated would have been eligible for the addition of ICI, 23% of the entire ES population in one Canadian province. After 1 or 2 cycles of chemotherapy an additional 11% of patients showed PS improvement to 0-1. While results of CASPIAN/IMpower133 are practice changing, the majority of patients will not meet clinical trial eligibility and clinical trials including patients with poor PS are necessary.